Analisis Aplikasi Teori Kepemimpinan dan Kinerja Pegawai Dalam Pelaksanaan BLUD di Puskesmas Bangkalan - Enggal Sari Maduratna; Nailufar Firdaus; WD YUNI M.USA (PROFESSIONAL HEALTH JOURNAL, 2023)
Performance appraisal is one of the main tasks of the Health Service who is responsible for the Health Service Sector. The performance evaluation of the Puskesmas consists of 3 assessments, that are assessment of the main program, management and innovation. Based on the results of a preliminary study by interviewing the Head of TU Sub-Division, information was obtained related to the uneven delegation of tasks by leaders to employees so that there were several employees who were overloaded with work. This has an impact on employee performance that is not optimal. The method used is qualitative with a case study approach and in-depth interviews with key informants and triangulation. The main informant was the Head of the Health Center, while the triangulation informants were the Head of Sub-Division of TU, ​​PJ UKM and UKP, PJ Networks and webs, PJ Facilities and infrastructure, PJ Quality, and PJ Finance. The results of the interviews obtained data that the application of leadership theory used in managing and leading employees has been adapted to the existing situations and conditions. As well as in terms of communication, motivation, knowledge, decision making and positive power. The same thing happened to the performance results, where commitment, discipline, responsibility and honesty began to increase among employees. Commitment, discipline, responsibility and honesty of employees are the results of the application of leadership theory that is applied properly. However, in implementing the need for human resources, especially those that are in accordance with educational qualifications and the needs of the Community Health Center, it is one of the things that needs to be improved in the future